PENGEMBANGAN PARIWISATA KOTA BUKITTINGGI DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH - Tegar Adrian; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The proliferation of new tourist attractions outside the city of Bukittinggi, of course, will have an effect on tourism in the City of Bukittinggi, both from the domain of visits and revenue. With the development of tourism that does not change, many tourists are likely to get bored with tourist attractions that just like that every year that may be able to reduce revenue in the city of Bukittinggi. Being aware of this requires a new development to attract the interest of tourists to travel to the city of Bukittinggi. This research is conducted to find out how the development of tourism conducted by the Department of Tourism Youth and Sports City of Bukittinggi to increase the original income area in the tourism sector and to determine what factors affect the development of tourism in increasing local revenue. According to the theory there are several kinds of analysis used for the development of tourism is planning (planning), organizing (organizing), actuating (movement), and Controlling (supervision). This research uses descriptive qualitative method that is analysis which try to give detailed description based on reality found in field. The results of this study indicate that the development of tourism Bukittinggi city affect the increase in local revenue. The tourism office of youth and sports of Bukittinggi city has made several improvements in the places of tourism objects in Bukittinggi, Kinantan Culture Park and Park Panorama Lobang Japan. However, the development has not been smooth, due to lack of budget from the government to do the development. So the development is not done thoroughly, due to lack of budget from the government. Keywords : Tourism Development, locally-generated revenue